The National Curricular Parameters for Secondary Education and the contextualization of the work world - Torres, Julio Cesar; Costa, Alessandra David Moreira da (FCL-UNESP Laboratório Editorial, 2007)
The paper discusses some aspects concerning the debate of the metamorphoses in the world of the work and its implications for the contextualization as a principle of curriculum organization for secondary education in Brazil. The contemporary paradigm of deep structural mutations in the way of production, when the importance of work as a category of analysis for the social theory has been questioned, makes us rethink the theoretical shades that base the interpretation of the social life. It is strengthened, at the National Curricular Parameters for Secondary Education, the idea that education is for life with a strong emphasis in the formation for the productive world, stimulating School to reflect and to discuss the impacts of these mutations for the formation of the young students.